Reassessment of natural expansive materials and their impact on freeze-thaw cycles in geotechnical engineering: a review - Oppong, Felix; Kolawole, Oladoyin (Frontiers in Built Environment, 2024)
The stabilization and application of expansive geomaterials are critical in geotechnical engineering. These naturally expansive materials exhibit complex hydro-chemo-mechanical properties because they undergo volumetric changes in response to variations in moisture content and/or temperature. The characteristic shrink-swell behavior of these materials makes their use problematic and plays a substantial role in influencing the stability of geo-infrastructure applications. However, there is a lack of comprehensive knowledge of the mechanisms and factors impacting their behavior to ensure mechanical integrity in natural and built infrastructure and geo-engineering projects. This work provides a comprehensive review of the intrinsic and extrinsic factors contributing to the shrink-swell behavior and expansion mechanisms of frost-heaving and natural-expansive geomaterials, such as expansive clays and sulfate minerals. We reviewed and synthesized peer-reviewed published works in various databases and academic repositories in the last 100 years. The influence of shrink-swell behavior of these geomaterials and the critical role they play in engineering infrastructure were highlighted, explicitly focusing on their involvement in geotechnical-related hazards, such as the freeze-thaw cycle, and the damage and sulfate-attack of geo-infrastructure. We analyzed the interactions between clay minerals, especially how bentonite enhances grout stability and acts as a buffer material in high-level nuclear waste repositories. The findings indicate that water interaction with geomaterials and concrete can cause about a 10% volume expansion when frozen. Also, the exposure of fractured rocks to low (≤0°C) and high (>0°C) temperatures can greatly change rock deformation and strength. Finally, gypsum interacting with water can theoretically increase in volume by 62% to form ice crystals. This forward-leading review presents the advantages, disadvantages, and unresolved issues of expansive natural geotechnical materials that improve the resiliency and sustainability of geological infrastructure.